'IT'S NOT SOMETHING ONE CAN DELIBERATELY SET OUT TO DO': CHRISTIAN WOLFF IN CONVERSATION. (19th December 2017) - Gardner, James; Fox, Christopher
ABSTRACT: In 2002 Christian Wolff was a guest composer at the Huddersfield Contemporary Music Festival and during the course of the festival he was interviewed by Christopher Fox and by James Gardner. Fox's interview took place before an audience in the Lawrence Batley Theatre on 25 November; Gardner's interview was recorded in private in the George Hotel, Huddersfield on 27 November, and edited excerpts from that recording were subsequently used in a programme produced by Radio New Zealand. The conversation presented here has been compiled by James Gardner from his transcriptions of the two interviews and presents a wide-ranging discussion of Wolff's musical preoccupations across every phase of his compositional career, from the early piano pieces of the 1950s, to his involvement with indeterminacy in the 1960s, to the political concerns evident in his music after 1970, to the works of the last three decades in which indeterminate and determinate methods of composition are combined.